Miguel Ángel Marin, Music on the Margin: Urban Musical Life in Eighteenth-Century Jaca (Spain) - Fernandes, Cristina (Revista Portuguesa de Musicologia, 2014)
Recensão: Miguel Ángel Marin, Music on the Margin: Urban Musical Life in Eighteenth-Century Jaca (Spain)